Weighted moving average-based differential UWB indoor localisation system for high external disturbance environment. Issue 3 (29th July 2019) - Gao, Qian; Shen, Chong; Chen, Xiaosi; Zhang, Kun
Time-based ultra-wideband (UWB) indoor localisation system is affected by clock offset, electromagnetic interference, NLOS and other external conditions, the localisation accuracy and stability will be greatly reduced. Differential GPS (DGPS) technology introduces a reference station, which transmits a pseudo range correction value to a GPS receiver for error correction, thereby largely reducing the localisation error to improve GPS localisation accuracy and localisation stability. In this paper a differential UWB localisation algorithm combined with weighted moving average is proposed by drawing on the experiences of differential GPS, focusing on clock offsets and propagation effects. At the same time, the differential UWB indoor localisation system based on TDOA algorithm is tested by Hainan EVK 2.0 experiments. The experiment results show that Differential UWB indoor localisation system can effectively improve the localisation precision and localisation stability, especially in the case of external disturbances, the overall localisation error is reduced by 23%.